Pengaruh Independensi, Mekanisme Corporate Governance dan Kualitas Audit Terhadap Integritas Laporan Keuangan (Jurnal Simki Economic, 2023)
The research objectives in this study were 1) to determine the effect of independence on the integrity of financial statements 2) to determine the effect of independent commissioners on the integrity of financial statements 3) to determine the effect of institutional share ownership on the integrity of financial statements 4) to determine the effect of the audit committee on the integrity of financial statements 5) to determine the effect audit quality on the integrity of financial statements. Research used associative. There are six variables used, namely independence, independent commissioners, institutional share ownership, audit committee, audit quality, and the integrity of financial reports. The population of this study were 13 automotive and component sub-sector manufacturing companies listed on the Indonesian stock exchange. The samples used were 39 financial reports. The data used is secondary data. The data collection method used in this study is the documentation of financial statements. The data analysis technique used in this study is the normality test, classical assumption test, coefficient of determination, multiple regression analysis, t test assisted by the Statistical Program For Special Science (SPSS). The results of this study indicate that the effect of independence has no positive effect, independent commissioners have no negative effect, institutional share ownership has a negative effect, audit committee has a positive effect, and audit quality has no positive effect on the integrity of financial statements.